Bioinformatics and experimental unveiling of TIMP1 as a novel therapeutic target in colorectal cancer ferroptosis - Tang, Chao; Li, Zhenhan; Song, Tianyu; Lu, Linming; Chen, Bofeng; Zhang, Tao; Zhang, Yi; Yang, Jie; Lao, Jianle; Chen, Hao (Frontiers in Oncology, 2025)
IntroductionColorectal cancer (CRC) remains a globally prevalent and lethal malignancy, with ferroptosis emerging as a novel cell death mechanism. This study aimed to elucidate the role of key genes in ferroptosis regulation and their impact on CRC malignancy.MethodsUsing bioinformatics and experimental methods, we identified TIMP1 as an oncogene that may promote CRC progression via ferroptosis, a pathway implicated in diverse diseases. TIMP1 expression was analyzed in TCGA CRC datasets and validated using the UALCAN database.ResultsTIMP1 was demonstrated as a critical ferroptosis-related gene in CRC, with elevated expression correlating with advanced pathological staging. Immunohistochemistry demonstrated significantly higher TIMP1 levels in CRC tissues compared to healthy controls. Functional assays revealed that TIMP1 knockdown enhanced ferroptosis sensitivity, suppressed CRC cell proliferation and migration, and reduced expression of ferroptosis regulators GPX4 and SLC7A11.ConclusionThese findings indicate that TIMP1 drives CRC malignancy through ferroptosis modulation, positioning TIMP1 as a potential therapeutic target and offering novel insights for CRC-targeted therapies.